1999
DOI: 10.1254/jjp.81.397
|View full text |Cite
|
Sign up to set email alerts
|

Antidiarrheal Effects of Zaldaride Maleate After Oral, Intravenous and Subcutaneous Administration to Rats.

Abstract: The antidiarrheal action of zaldaride maleate (ZAL) after oral, intravenous and subcutaneous administration was examined to determine whether ZAL acts systemically or locally in the intestine of rats. Oral administration of ZAL inhibited castor oil- and 16,16-dimethyl prostaglandin E2-induced diarrhea; however, intravenous or subcutaneous administration of ZAL was ineffective. When ZAL was orally administered, the area under the plasma concentration time curve of the compound was lower than that of ZAL followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…This new experimental model of TD led to some of the symptoms observed in humans: diarrhea, fever, body weight decrease due to reduction of food and water consumption and production of inflammatory cytokines [1,2,6]. These symptoms last for 2-3 days after induction of TD, in contrast with the existing model of diarrhea induced by an oral administration of castor oil, which only produces diarrhea lasting for 4 h [40,[42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This new experimental model of TD led to some of the symptoms observed in humans: diarrhea, fever, body weight decrease due to reduction of food and water consumption and production of inflammatory cytokines [1,2,6]. These symptoms last for 2-3 days after induction of TD, in contrast with the existing model of diarrhea induced by an oral administration of castor oil, which only produces diarrhea lasting for 4 h [40,[42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…No realistic experimental models of TD exist. The castor oil-induced diarrhea model is the most widely used experimental model to develop anti-diarrheal substances [42][43][44][45][46][47]. It induces a severe secretory diarrhea during the first hour after the oral administration of castor oil and semi-solid diarrhea during the next 3 h. It is due to one of castor oil ingredients, ricinoleic acid, which induces the secretion of prostaglandins E2 in the gut lumen and also increases the net secretion of the water and electrolytes into the small intestine.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of male rats and the use of an oral route were based on earlier studies to avoid the gender discrepancies in rats response to an anti-diarrhoeal agent and a fact that such agents were known to act locally in the intestinal tracts (Aikawa et al, 1999(Aikawa et al, , 2000. Results showed that the extract have some activity in all the models used.…”
Section: Discussionmentioning
confidence: 99%